Teacher Education in Yugoslavia. Issue 1 (1st December 2001) - Radulovich, Lidija; Rajovich, Vera
Pre- and in-service teacher education in Yugoslavia has no structure and pattern providing the system to cover all teachers coming from diverse background. Current situation of teacher education in Yugoslavia is presented in this paper. Its main characteristics and difficulties are outlined in relation to 1) the legislation and normative and 2) users needs. After analyzing the current situation, we present an agenda for reform and development that should enable teacher education to respond to the changing needs of Yugoslavia. Throughout the paper we refer to the initial and continuing professional development of history teachers: they are one element in the overall equation.